The impact of task simplification in skill acquisition for young children from a simplexity approach - Jia Yi Chow; Wan Ting Loh; Karen Lai Fong Low; Ludovic Seifert (Acta Psychologica)
Informational constraints play an important role in guiding skill acquisition for learners. From an Ecological Dynamics perspective, skill acquisition is seen as an interplay of the key interactions between learners and environment to support the emergence of different movement possibilities in a skill acquisition context. However, simple information constraints can support the development of complex movements. Simplexity allows for functional complex movements to be produced underpinned by simple control mechanisms. In this study, an investigation was undertaken to examine the impact (pre, post, retention and transfer tests) of task simplification to support the acquisition of a discrete multi-articular movement (badminton serve) with reference to performance outcome and movement behaviours in young children (11 to 12 years old) in the context of Physical Education over a 4-week period. It was found that participants provided with simplified informational constraints (Nonlinear Pedagogy condition) learnt the badminton serving task as well as participants provided with explicit information constraints and with a focus on repeating consistent outcome (Linear Pedagogy condition). In addition, participants from the Nonlinear Pedagogy condition explored and adapted movement behaviours to achieve the same learning outcome as the Linear Pedagogy condition. The use of simplified informational constraints could scaffold the acquisition of a complex movement task, providing support for simplexity in the skill acquisition process.